Antibacterial and cytotoxic effects of fresh bovine amniotic membrane with hydroxyapatite (BAM-HA): a laboratory experiment - Octarina, Octarina; Berliana, Stefhanie; Kalangit, Ruth Belatriks (Padjadjaran Journal of Dentistry, 2024)
Introduction: Bacterial infections, particularly by Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) and Porphyromonas gingivalis (P. gingivalis), can worsen alveolar bone resorption after tooth extraction. The capability of Bovine Amniotic Membrane-Hydroxyapatite (BAM-HA) biocomposite to reduce this resorption has been explored. However, before clinical use, cytotoxicity testing is imperative to ensure its biocompatibility. The aim of the study was to assess both the antibacterial effects and cytotoxicity of the BAM-HA biocomposite to ensure its suitability for clinical use biocompatibility of the BAM-HA biocomposite before its clinical application. Methods: The laboratory-based research involved testing BAM combined with HA powder in 4:1 and 4:2 ratios via freeze-drying and underwent antibacterial tests against A. actinomycetemcomitans and P. gingivalis, using the plate count method. Cytotoxicity tests were performed on HGF cells, including negative control, positive control, BAM-HA (4:1), and BAM-HA (4:2) groups, with statistical analysis conducted using One-Way ANOVA and Post Hoc Bonferroni and Tukey tests. Results: Antibacterial tests against A. actinomycetemcomitans revealed significant reduction in colony count with BAM-HA ratios 4:1 (129.0 ± 12.7 CFU/mL) and 4:2 (77.3 ± 15.5 CFU/mL) compared to the negative control (186.6 ± 27.5 CFU/mL). Similar reductions were observed for P. gingivalis, with BAM-HA ratios 4:1 (51.3 ± 6.6 CFU/mL) and 4:2 (3.1 ± 1.5 CFU/mL) compared to the negative control (117.3 ± 22.0 CFU/mL). Cytotoxicity tests showed no significant differences in HGF cell viability and IC50 values between the negative control and BAM-HA (4:1) or BAM-HA (4:2) groups. Conclusion: The BAM - HA biocomposite shows antibacterial effects against A. actinomycetemcomitans and P. gingivalis. Moreover, BAM - HA ratios of 4:1 and 4:2 do not induce cytotoxic effects on human gingival fibroblasts, suggesting potential biocompatibility for clinical applications.KeywordA. actinomycetemcomitans, antibacterial effects, BAM-HA biocomposite, cytotoxicity, P. gingivalis